Awareness of sudden infant death syndrome and choice of infant’s sleep position among mothers in Enugu, Southeast Nigeria - Ikenna, Ndu K.; Osita, Ezenwosu U.; Benedict, Edelu O.; Nnamdi, Ogbuka F.; O. C, Ndagubam; Isaac, Asinobi N.; Ogechukwu, Amadi F.; Ifeyinwa, Okeke B.; Uchenna, Ekwochi; Chidiebere, Osuorah D. I. (Indian Journal of Child Health, 2019)
Background: Sudden infant death syndrome (SIDS) has been identified as a common cause of death among infants. However, in countries that introduced risk reduction and safe sleep campaigns, there has been a significant decline in SIDS-related deaths. Unfortunately, there has been little interest in SIDS by researchers in Nigeria. Objective: The aim of the study was to determine the level of parental awareness and awareness of the risk reduction measures about SIDS in Nigeria and to further determine the level of practice of the measures. Materials and Methods: This was a hospital-based cross-sectional study conducted over a 6-month period from April 2016 to September 2016 in the Well Baby Clinic of Enugu State University Teaching Hospital, Enugu. Four hundred and one respondents were enrolled, and interviewer-based questionnaires administered. Results were presented as percentages. IBM Statistical Package for the Social Sciences version 20 was used for data analysis and statistical significance was set at p